Liberalization against democracy : the local politics of economic reform in Tunisia - King, Stephen J. (Stephen Juan), 1961- (Indiana series in Middle East studies., 2003)
" ... A very important contribution to contemporary debates on economic and political reform in developing countries. Based on interviews King conducted himself, this is an honest, unvarnished examination and critique of propositions that are treated like gospel."--Lisa AndersonIn Liberalization against Democracy, Stephen J. King argues that, in contrast to prevailing views, pro-market economic reforms in Tunisia did not foster democratization. Instead, state-led economic liberalization fa